2004
DOI: 10.1016/j.eupc.2004.08.005
|View full text |Cite
|
Sign up to set email alerts
|

A new treatment for atrial fibrillation based on spectral analysis to guide the catheter RF-ablation

Abstract: The RF-ablation of AF nests decreasing the fibrillar/compact myocardium ratio eliminated 94% of the paroxysmal AF in patients in the FU of 9.9 +/- 5 months. The AF nests may be easily identified by spectral analysis and seem to be the real AF substrate. Paroxysmal AF may be cured or controlled by applying RF in several places outside the PV and, thereby, avoiding PV stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
166
1
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(190 citation statements)
references
References 27 publications
6
166
1
7
Order By: Relevance
“…35,37 Although ganglionated plexi ablation significantly reduces AF recurrence, the long-term success rate is lower than after PVI. [35][36][37][38][39][40][41] Interestingly, in addition to PVI, the suppression of ganglionated plexi response -particularly that observed during cryoablation -may reduce AF recurrence. 40,41 Although many authors believe that additional ablations are required for non-paroxysmal AF or some paroxysmal AF, no randomised studies have consistently shown which strategy to use.…”
Section: Pathophysiology Of Atrial Fibrillation and Atrial Fibrillatimentioning
confidence: 99%
See 2 more Smart Citations
“…35,37 Although ganglionated plexi ablation significantly reduces AF recurrence, the long-term success rate is lower than after PVI. [35][36][37][38][39][40][41] Interestingly, in addition to PVI, the suppression of ganglionated plexi response -particularly that observed during cryoablation -may reduce AF recurrence. 40,41 Although many authors believe that additional ablations are required for non-paroxysmal AF or some paroxysmal AF, no randomised studies have consistently shown which strategy to use.…”
Section: Pathophysiology Of Atrial Fibrillation and Atrial Fibrillatimentioning
confidence: 99%
“…34 It has been suggested that ganglionated plexi may have a role in the initiation and maintenance of both paroxysmal and non-paroxysmal AF. [35][36][37][38][39][40][41] Localisation is usually performed on the endocardium either anatomically, by vagal response following high-frequency stimulation, or by Fourier transform in sinus rhythm. 35,37 Although ganglionated plexi ablation significantly reduces AF recurrence, the long-term success rate is lower than after PVI.…”
Section: Pathophysiology Of Atrial Fibrillation and Atrial Fibrillatimentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, following PVI and AFN ablation,most recurrences are caused by an organized, typically fast atrial tachycardia. This residual tachycardia often appears as a transitional rhythm during AF ablation upon its organization or termination,[ Figure 1] By using spectral analysis with Fast Fourier Transform (FFT) we have found that this tachycardia is present during AF, before ablation, [25] which we have named "Background Tachycardia" (BT) [22], [26], [27] . Rapid atrial pacing following PVI and AFN ablation can also commonly induce one or more of these organized atrial tachycardias.…”
mentioning
confidence: 99%
“…Pulmonary vein isolation (PVI) [3], [4] is recognized as the cornerstone for paroxysmal atrial fibrillation (AF) ablation [5], [6], [7] but insufficient as a stand-alone ablation approach for LSAF [8], [9] .The adjunct of linear ablation lesion sets [10], [11], [12] ; ablation of complex fractionated atrial electrograms (CFAE) [13], [14] ; extensive ablation including the left atrial (LA) posterior wall [15] , superior vena cava (SVC) [16] , coronary sinus and LA appendage or even vagal denervation [17], [18] may improve outcomes slightly but compromises procedural complexity and safety [19], [20], [21] . We have found that the AF Nests (AFN) ablation had a favorable impact on the long-term outcome after a single procedure [22], [23] . It decreased overall recurrences as compared to our conventional PV antral isolation plus CFAE ablation [24] .…”
mentioning
confidence: 99%